2021
DOI: 10.3390/s21093217
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Pressure Variability and Asymmetry in Elderly Performing 60-Minute Treadmill Brisk-Walking: Paving the Way towards Fatigue-Induced Instability Assessment Using Wearable In-Shoe Pressure Sensors

Abstract: Evaluation of potential fatigue for the elderly could minimize their risk of injury and thus encourage them to do more physical exercises. Fatigue-related gait instability was often assessed by the changes of joint kinematics, whilst planar pressure variability and asymmetry parameters may complement and provide better estimation. We hypothesized that fatigue condition (induced by the treadmill brisk-walking task) would lead to instability and could be reflected by the variability and asymmetry of plantar pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…12 (b), TOTEX was also extracted every 30 steps to eliminate the impact of local time-related effect by expanding the extraction interval. The continuous downward trend of TOTEX indicated that the gait integrity of subject gradually declines over time, which might be associated with physical fatigue, because fatigue is also a gradual process and occurs in repeated or continuous muscle activation [37], such as walking test [38] and action repetition [39]. In addition, some characteristics of gait have been proved to change owing to fatigue [38]- [40], and the elderly are more prone to fatigue [41].…”
Section: ) Statistical Results Of Temporal Consistency Related Featuresmentioning
confidence: 99%
“…12 (b), TOTEX was also extracted every 30 steps to eliminate the impact of local time-related effect by expanding the extraction interval. The continuous downward trend of TOTEX indicated that the gait integrity of subject gradually declines over time, which might be associated with physical fatigue, because fatigue is also a gradual process and occurs in repeated or continuous muscle activation [37], such as walking test [38] and action repetition [39]. In addition, some characteristics of gait have been proved to change owing to fatigue [38]- [40], and the elderly are more prone to fatigue [41].…”
Section: ) Statistical Results Of Temporal Consistency Related Featuresmentioning
confidence: 99%
“…Cancer is associated with an increased risk for falls [ 8 ], and neurotoxic chemotherapy is among the contributors [ 9 , 10 ]. Altered patterns of plantar pressure distribution are published in diabetic and experimental neuropathies [ 11 , 12 ], as well as in aging [ 13 ], but spatial or temporal dynamics are rarely published in chemotherapy-induced peripheral neuropathy (CIPN). When pressure- or force-sensing technology is used to quantify CIPN-linked gait abnormalities, typical outcome variables are gait speed and the length and duration of each step or stride [ 10 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Common temporal gait parameters such as walking velocity, stride length, foot angle, gait variability, cadence, and foot clearance can currently be obtained in real time by automatic calculation in the microprocessor of an IMS [ 4 , 5 ]. In contrast, temporal gait parameters concerning bilateral lower limbs (GPBLLs) play more important roles in healthcare or daily activity monitoring applications, such as evaluation of walking ability [ 4 ], metabolic evaluation [ 6 ], daily fatigue monitoring [ 7 ], and alcohol use monitoring [ 8 ]. These parameters include the double support time (DST), which is defined as the duration when both bilateral lower limbs touch the ground in one gait cycle (GC), and the symmetry index of stride time ( SIS tr ) and symmetry index of stance phase time ( SIS ta ) between the two limbs.…”
Section: Introductionmentioning
confidence: 99%
“…These GPBLLs are important because they capture the interaction of the two feet and are essential predictors for estimating certain deep gait parameters, such as gait asymmetry, lower limb muscle strength, and muscle strength transition ability from one limb to the other [ 5 , 6 , 9 ]. Furthermore, these deep gait parameters are significant predictors for metabolic monitoring, fatigue assessment, walking ability, body functions, and alcohol monitoring [ 5 , 6 , 7 , 9 , 10 , 11 , 12 ]. To expand the potential use of IMSs in healthcare or daily activity monitoring applications for healthy subjects, we believe it is necessary to conduct automatic measurement of these GPBLLs by an IMS.…”
Section: Introductionmentioning
confidence: 99%